Variability of mesospheric water vapor above Bern in relation to the 27-day solar rotation cycle. (June 2016) - Lainer, Martin; Hocke, Klemens; Kämpfer, Niklaus
Abstract: Many studies investigated solar–terrestrial responses (thermal state, O3, OH, H2 O) with emphasis on the tropical upper atmosphere. In this paper the focus is switched to water vapor in the mesosphere at a mid-latitudinal location. Eight years of water vapor profile measurements above Bern ( 46.88 ° N / 7.46 ° E ) are investigated to study oscillations with the focus on periods between 10 and 50 days. Different spectral analyses revealed prominent features in the 27-day oscillation band, which are enhanced in the upper mesosphere (above 0.1 hPa, ∼ 64 km ) during the rising sunspot activity of solar cycle 24. Local as well as zonal mean Aura MLS observations support these results by showing a similar behavior. The relationship between mesospheric water and the solar Lyman- α flux is studied by comparing the similarity of their temporal oscillations. The H2 O oscillation is negatively correlated to solar Lyman- α oscillation with a correlation coefficient of up to − 0.3 to − 0.4, and the phase lag is 6–10 days at 0.04 hPa . The confidence level of the correlation is ≥ 99 % . This finding supports the assumption that the 27-day oscillation in Lyman- α causes a periodical photodissociation loss in mesospheric water. Wavelet power spectra, cross-wavelet transform and wavelet coherence analysis (WTC) complete our study. More periods of high common wavelet power of H2 O and solar Lyman- α are present when amplitudes of the Lyman- α flux increase. Since this is not a measure of physical correlation a more detailed view on WTC is necessary, where significant (two sigma level) correlations occur intermittently in the 27 and 13-day band with variable phase lock behavior. Large Lyman- α oscillations appeared after the solar superstorm in July 2012 and the H2 O oscillations show a well pronounced anti-correlation. The competition between advective transport and photodissociation loss of mesospheric water vapor may explain the sometimes variable phase relationship of mesospheric H2 O and solar Lyman- α oscillations. Generally, the WTC analysis indicates that solar variability causes observable photochemical and dynamical processes in the mid-latitude mesosphere. Abstract : Highlights: Solar variability causes observable photochemical and dynamical processes in mid-latitude mesosphere. Enhanced mesospheric H2 O wave activity in the 27-day period band above 0.1 hpa. Cross-correlations of −0.3 to −0.4 between solar Lyman- α and MIAWARA H2 O are found. H2 O response phase lag of roughly 6–10 days to the solar forcing. Lyman- α oscillations induce discernible anti-correlations in H2 O after solar superstorm in 2012.